Canada : Financial Sector Assessment Program-Technical Note-Bank Resolution and Crisis Management. (IMF Staff Country Reports; Country Report ;, 2020)
This Technical Note on Financial Safety Net and Crisis Management for the Canada presents the findings and recommendations made in the Financial Sector Assessment Program for Canada in the areas of bank resolution and crisis management. The note is based on the findings of the mission conducted during October 29-November 14, 2018. The note highlights that Canada has maintained financial stability for a long period of time. Strong institutional settings, effective supervision, and sound financial sector policies have succeeded in preventing crisis situations. The last bank failure in Canada occurred more than twenty years ago. However, the lack of crisis events does not diminish the need for preparation and for revisions to the existing framework. A substantial part of the financial system is covered by federal crisis management and safety net arrangements that are well-established. Coordination among the federal agencies is strong, underpinned by inter-agency committees. The note recommends that the ongoing work of the authorities in completing and enhancing their contingency plans and implementing testing and readiness programs should be continued.